Detection of Streptococcus pyogenes from Throat Swab in Acute Pharyngitis Patients - Ibnu Tsabit Maulana; Imam Megantara; Ike Rostikawati Husen (Althea Medical Journal, 2016)
Background: Pharyngitis is an inflammation of throat that may be caused by viral and bacteria. Although Streptococcus pyogenes is only responsible for 5−15% of cases of pharyngitis in adults. Antibiotics are highly prescribed for this infection, thus it could lead to antibiotic resistance. The main reason for antibiotic overprescription is the difficulty to obtain a rapid and correct etiological diagnosis. This study aimed to determine the frequency of Streptococcus pyogenes from throat swab in patient with acute pharyngitis in Padjadjaran Clinic.Methods: This study was a descriptive study. Specimen was taken from the patients in Padjadjaran Clinic on September until October 2014. Thirty-five patients with acute pharyngitis that met the selection criteria were recruited for throat swab. Then, specimens obtained were performed an identification testing to determine whether there was a colonization of Streptococcus pyogenes. Results: Thirty five patients were found with acute pharyngitis consist of 14 male and 21 female, with age ranged between 16−34 years old. From the identification testing result, Streptococcus pyogenes was not found from throat swabs of patient with acute pharyngitis in Padjadjaran Clinic.Conclusions: This study found no colonization of Steptococcus pyogenes in throat swabs of acute pharyngitis patients in Padjadjaran Clinic, however Streptococcus pyogenes was not the causative fact of acute pharyngitis. [AMJ.2016;3(1):69–72] DOI: 10.15850/amj.v3n1.716